Myopia: histology, clinical features, and potential implications for the etiology of axial elongation - Jonas, Jost B.; Jonas, Rahul A.; Bikbov, Mukharram; Wang, Ya Xing; Panda-Jonas, Songhomitra (Progress in retinal and eye research, 2023)
Myopic axial elongation is associated with various non-pathological changes. These include a decrease in photoreceptor cell and retinal pigment epithelium (RPE) cell density and retinal layer thickness, mainly in the retro-equatorial to equatorial regions; choroidal and scleral thinning pronounced at the posterior pole and least marked at the ora serrata; and a shift in Bruch's membrane opening (BMO) occurring in moderately myopic eyes and typically in the temporal/inferior direction. The BMO shift leads to an overhang of Bruch's membrane (BM) into the nasal intrapapillary compartment and BM absence in the temporal region (i.e., parapapillary gamma zone), optic disc ovalization due to shortening of the ophthalmoscopically visible horizontal disc diameter, fovea-optic disc distance elongation, reduction in angle kappa, and straightening/stretching of the papillomacular retinal blood vessels and retinal nerve fibers. Highly myopic eyes additionally show an enlargement of all layers of the optic nerve canal, elongation and thinning of the lamina cribrosa, peripapillary scleral flange (i.e., parapapillary delta zone) and peripapillary choroidal border tissue, and development of circular parapapillary beta, gamma, and delta zone. Pathological features of high myopia include development of macular linear RPE defects (lacquer cracks), which widen to round RPE defects (patchy atrophies) with central BM defects, macular neovascularization, myopic macular retinoschisis, and glaucomatous/glaucoma-like and non-glaucomatous optic neuropathy. BM thickness is unrelated to axial length. Including the change in eye shape from a sphere in emmetropia to a prolate (rotational) ellipsoid in myopia, the features may be explained by a primary BM enlargement in the retro-equatorial/equatorial region leading to axial elongation.
Online verfügbar: 28. Dezember 2022, Artikelversion: 12. September 2023
Gesehen am 06.12.2023